ANALISIS SISTEM PEMBERIAN UPAH TERHADAP TINGKAT KESEJAHTERAAN EKONOMI KELUARGA BURUH TANI KARET DI DESA BATURADEN - Pradita, Diaz Meydi; Pusvita, Ema; Septianita, Septianita (Universitas Galuh, 2023)
In the midst of unstable rubber prices, rubber farm laborers in Baturaden Village still depend on the wage system that is applied. There are two categories of wage systems, the first 1:1 and 1:2. Of course there is a classification in determining the two wage systems which both have advantages and disadvantages. The purpose of this study is to determine the level of family economic welfare and income inequality between farm laborers with a 1:1 and 1:2 wage system. The research location was purposively selected because most of the people in Baturaden Village work as farm laborers. The research method used was survey method with sampling method using stratified random sampling. Data collection used primary data obtained from interviews and secondary data collected from BPS, Baturaden Village Office, etc. The data was processed using the 2015 BPS indicators to measure the level of welfare and the gini ratio to measure the level of income inequality among farm laborers. Based on the results, it was found that the welfare level of each farm laborer was moderate and so was the income inequality which was also in the moderate category. This is because farm laborers have turned their brains to look for side jobs to meet the economic needs of their families. because if they continue to rely only on income as rubber farm laborers they claim to have difficulty meeting household needs where the price of basic goods is getting more and more expensive.